1982
DOI: 10.1136/gut.23.12.1068
|View full text |Cite
|
Sign up to set email alerts
|

Changes in plasma half-life and clearance of 3H-25-hydroxyvitamin D3 in patients with intestinal malabsorption.

Abstract: SUMMARY The plasma disappearance of intravenously administered tracer doses of tritiumlabelled 25-hydroxyvitamin D3 (250HD3) was studied in six normal subjects and in 15 patients with intestinal malabsorption. The plasma half-life was significantly shorter and the clearance rate significantly greater in the group with malabsorption compared with the controls. One explanation for this increased elimination could be interruption of an enterohepatic circulation of 250HD occurring in subjects with malabsorption an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 15 publications
1
20
0
Order By: Relevance
“…Over the past 25 years, research has shown that both high-fiber diets and intestinal malabsorption reduce the serum half-life of 25(OH)D by approximately one-third [242,243]. Further, experiments in rats have demonstrated that an elevation in serum 1,25(OH) 2 D concentrations, either by exogenous administration or endogenously through a low-calcium diet, increases the metabolic clearance rate of 25(OH)D without altering its rate of production [244e246].…”
Section: The Pathogenetic Spectrum Of Nutritional Ricketsmentioning
confidence: 99%
“…Over the past 25 years, research has shown that both high-fiber diets and intestinal malabsorption reduce the serum half-life of 25(OH)D by approximately one-third [242,243]. Further, experiments in rats have demonstrated that an elevation in serum 1,25(OH) 2 D concentrations, either by exogenous administration or endogenously through a low-calcium diet, increases the metabolic clearance rate of 25(OH)D without altering its rate of production [244e246].…”
Section: The Pathogenetic Spectrum Of Nutritional Ricketsmentioning
confidence: 99%
“…Vitamin D 2 (ergocalciferol) is plant derived and is obtained through the diet or supplementation. For practical purposes, both forms of vitamin D can be considered bioequivalent and undergo the same metabolism, initially to 25- Assessment of vitamin D status is ascertained through the measurement of serum 25(OH)D concentration, rather than 1,25(OH) 2 D, since the former is the most stable and plentiful metabolite and has a half-life of 3 weeks [2]. The precise threshold for defining vitamin D deficiency and vitamin D insufficiency has been a matter of debate, but bone disease resulting from vitamin D deficiency is generally associated with serum 25(OH)D concentrations lower than 10 ng/mL.…”
Section: Introductionmentioning
confidence: 99%
“…Hiroaki ITOH 1 * , Ippei MORI 1, 2 , Yuki MATSUMOTO 1 , Syou MAKI 1 and Yasutaka OGAWA 1 25-Hydroxyvitamin D (25OHD), a major component of circulating vitamin D metabolites whose biological half-life in blood (2-5 wk in normal subjects) [10][11][12][13][14] is substantially longer than that of vitamin D itself (24 h) 10) , is commonly used as an indicator of individuals' vitamin D status 15) . Exposure to solar ultraviolet (UV) B irradiation changes 7-dehydrocholesterol to previtamin D by photosynthesis in the skin.…”
Section: Vitamin D Deficiency and Seasonal And Inter-day Variation Inmentioning
confidence: 99%